Dimensi Pasar Domestik Komoditas Padi dan Beras (Telaah Struktur Pasar di Kecamatan Sunggal, Deli Serdang) - Wulan Dayu; Windu Anggara; Isnaini Harahap (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2023)
The market structure and pattern of rice commodity distribution are closely related to the income level of rice farmers. The huge difference in the prices of unhusked rice and rice in Sungal Sub-District has reduced the wealth of farmers, considering that most farmers are both producers and consumers of rice. In particular, this study aims to: 1) describe the pattern of distribution of rice and rice raw materials from farmers to final consumers in Sunggal District; and 2) analyze how much profit margin each marketer gets in the rice distribution chain in Sunggal District. This study involved 70 farmers, 8 middlemen, 4 rice mills, 7 wholesalers, and 5 retailers using a simple random sampling technique. The distribution pattern and unhulled rice market margin were used to analyze the data descriptively. The results of a survey conducted in Sungal District showed two patterns of distribution, namely: Distribution Pattern I: Rice Mills????Middlemen????Distribution????Farmers????Consumers; and Distribution Pattern II: Farmers????Rice Milling????Collectors????Retailers????Consumers. So in this study, it can be concluded that the highest marketing margins were found in rice mills (34.37%), collectors (10.29%), middlemen (8.50%), and retailers (7.52%) from marketing margins in the market structure and distribution of rice commodities